Legal Nature of the Central Criminal Court - محمود صباح سامي; جبر هناء عبد العزيز (Journal of Legal Sciences, 2019)
In this paper, we discussed the legal nature of the Central Criminal Court with two demands: the first relates to the legal basis of the Central Criminal Court, and the second is related to the criminal justice system. With regard to the first demand, we have highlighted the stage after the change of the political system in Iraq in 2003 and the subsequent assumption of the US Governor for Civil Administration Affairs in the country and the issuance of a number of resolutions, including what we discussed in the first section (the first legislation No. 13 of 2003 ), Which included twenty-three sections, some showing how the Central Court was formed and the most important rules governing it. In addition, we have referred to some of the defects of formality and some of them beyond the logical sequence of its sections and the non-standardization of terms with regard to the legal name of the court. We also referred to the substantive defects of the law, including the uniqueness of the administrative authority of the destruction authority by appointing and exempting the judiciary . We then moved to the second section, which included (second legislation no. 13 of 2004), the most important of which was the transfer of the functions and functions of the government to the Iraqi Transitional Administration under the Iraqi State Administration Law for the transitional phase canceled under Article 142 of the Iraqi Constitution, We have identified weaknesses in this legislation, including the lack of a text on the formation of a central court of events. In both sections, we have concluded that the legal basis for the establishment of the Central Criminal Court is Act No. 13 of 2003, repealed, and amended Law No. (31) of 2004 issued by the Coalition Provisional Authority in Iraq. If we want to talk about the central court, we must define the type of judiciary (whether ordinary or special) that governs the legal nature of the central criminal court, so we had to show what The ordinary judiciary and this is what we mentioned in the first section under the title (ordinary judiciary), and the second section (special or exceptional judiciary), clarifying the views in favor of the nature of the court, whether ordinary or special court. We then presented what we are going through as a researcher that the Central Criminal Court agrees with the courts of each jurisdiction to adjudicate certain types of crimes, but it differs from them otherwise, and we have reached the possibility of determining the legal nature of the Central Criminal Court as an ordinary court of natural jurisdiction, With its special competence, it is a specialized criminal court or a competent court, not a special or an exceptional one, explaining our opinion in this opinion.